THE CORRELATION BETWEEN GRAMMAR MASTERY AND WRITING ABILITY ON MIDWIFERY STUDENTS OF STIKES PEMBINA PALEMBANG IN 2019 - Arief Pamuji (Universitas Tridinanti Palembang, 2020)
The purpose of this study was to determine the relationship between grammar mastery and writing ability on midwifery students at STIKES Pembina Palembang. The population in this study was 22 of fourth semester students of the midwifery study program, STIKES Pembina and study sample were all the population that using total sampling. The data were obtained by using 2 tests, namely the TOEFL (structure and written expression) test and the English writing test. To verify the hypothesis, the data were analyzed by using correlation analysis and using the Statistical Product and Service Solution (SPSS) software version 21.00. Based on data analysis the correlation coefficient on grammar mastery and writing ability was 0.790, this showed that the relationship had a very high relationship and the value of r- is higher than the critical value of r null hypothesis table (Ho) was rejected and consequently, the research hypothesis (H1) received.Keywords: Grammar Mastery, and Writing Ability